Age, growth, and reproductive biology of the Atlantic spadefish Chaetodipterus faber in southern Brazil - Soeth, Marcelo; Favaro, Luis Fernando; Spach, Henry Louis; Daros, Felippe Alexandre [UNESP]; Woltrich, Ana Emilia; Correia, Alberto Teodorico (Springer, 2019)
This is the first study to investigate the age, growth and reproductive biology of the Atlantic spadefish Chaetodipterus faber in southern Brazil. A total of 625 individuals [total length (TL) ranging from 7mm to 510mm] were sampled at the Paranagua Estuarine Complex (PEC) and adjacent coastal areas over a year (August 2015 to July 2016). Age estimation based on sagittal otolith cross section showed that C. faber has a 17-year longevity close to its southern distributional limit, two times greater than previously reported from the North AtlanticOcean. Sexual growth dimorphism was not evident as the male:female sex ratio was 1:1.17. The species displayed asymptotic growth. Fitted von Bertalanffy growth function estimates for all individuals were L=508.81mm, k=0.22year(-1), and t(0)=-0.05year. The histological gonadal examination and gonado-somatic index indicated that C. faber is a batch spawner with a main reproduction period from October to January in subtropical latitudes at 25 degrees S. Postovulatory follicles were often recorded in the ovaries of spawning capable individuals indicating a high frequency of spawns over the reproductive period. The data also suggest that estuaries are important reproductive areas for this species that most likely exhibits a seasonal movement for spawning aggregation purposes. Females mature approximately 0.5years later than males and are capable of spawning just prior to two years old. Fishery closures during the spawning season and fishing size restrictions should be used to manage the C. faber stock in southern Brazil. The effects of current harvest levels are unknown and warrant further investigation to assist management decisions.
Keywords: Ephippidae; Growth modelling; Reproduction; Sexual maturity; South Atlantic